Consequences of IT Transformations - O. V. Gutorovich; V. N. Gutorovich (Дискурс, 2019)
Introduction. The driving force of the modern society development is information technology transformations. They determined the beginning of qualitative transformations of not only the world order, but also many essential features of the state. Because of this, the study of changes in the sphere of political power and government, as well as the class structure of society, acquires special significance.Methodology and sources. The conclusions presented in this paper are based on the methodology of analytical and critical generalization in the field of social philosophy, as well as special theories and approaches, among which should be noted the neoinstitutional approach, the theories of the post-industrial and network society.Results and discussion. The introduction of digital technology is stacked for the state in two ways. The state receives not only new mechanisms for monitoring, accounting, control, pressure, and verification of the population, but also a high degree of citizen involvement in the state governing process. The consequence of a high degree of activity of civil structures may be the decentralization of state power and the redistribution of powers. A significant danger to the state is the network governing structure that requires all its participants to connect to the information channels. Having taken root in the governing environment, the network principle will come into conflict with the traditional chain of command, which will inevitably lead to the dispersion of its functions and blur the old governing schemes. There are the formation and further confrontation of two classes, which can be conventionally called the "higher" and "lower" classes in the logic of the development of the modern information society. Thus, in the course of the study, the problem of the transformation of the state institution in the conditions of information technology transformations was analyzed, and the issue of the formation of a new class structure was also raised.Conclusion. The age of information technology does not just create a new society, but it determines its essence, structure, basic characteristics, determines and sets parameters of its development.